Portfolio analytics : an introduction to return and risk measurement - Marty, Wolfgang (Springer Texts in Business and Economics, 2013)
This textbook first introduces the reader to return measurement and then goes on to compare the time-weighted rate of return (TWR) with the money-weighted rate of return (MWR). To emphasize the importance of risk in conjunction with return, different tracking errors are analyzed and ex-post versus ex-ante risk figures are compared. The author then proceeds to modern portfolio theory (MPT) and illustrates how the constraints interfere substantially in the construction of optimized portfolios. As a conclusion, the book provides the reader with all the essential aspects of investment controlling.